2012
DOI: 10.2527/jas.2011-4282
|View full text |Cite
|
Sign up to set email alerts
|

Consumer assessment of beef strip loin steaks of varying fat levels

Abstract: A consumer study was conducted in Lubbock, Texas, to determine the effects of fat level of beef strip steaks on the palatability traits of tenderness, juiciness, flavor liking, and overall liking, while further investigating the window of acceptability for fat content of beef. Thirty beef strip loins were selected by trained personnel to equally represent USDA Prime, High Choice (upper 1/3 Choice), Low Choice (lower 1/3 Choice), Select, and Standard. Proximate analysis was conducted on all strip loins to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
87
3
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 16 publications
13
87
3
3
Order By: Relevance
“…These findings are consistent with numerous recently published reports (O'Quinn et al, 2012;328 Hunt et al, 2014;Corbin et al, 2015) and are consistent with their role in meat quality 329 acceptance. It has been reported that the most important attributes that influence acceptability 330 are tenderness and juiciness (Butler, Poste, Mackie & Jones, 1996;Zimoch & Gullett, 1997) …”
supporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with numerous recently published reports (O'Quinn et al, 2012;328 Hunt et al, 2014;Corbin et al, 2015) and are consistent with their role in meat quality 329 acceptance. It has been reported that the most important attributes that influence acceptability 330 are tenderness and juiciness (Butler, Poste, Mackie & Jones, 1996;Zimoch & Gullett, 1997) …”
supporting
confidence: 93%
“…Recent studies by Corbin et al (2015) and O'Quinn et al (2012) show similar findings to the 345 latter. Except for one data set (the French protocol with beef from young bulls cooked at 346 55°C), normal and abnormal beef flavour were negatively correlated.…”
supporting
confidence: 74%
“…Despite similar (P > 0.05) consumer palatability scores and acceptability percentages between TC and SE in our study, differences in palatability between quality grades in U.S. treatments have been previously reported when comparing strip loin tenderness scores (Corbin et al, 2015;O'Quinn et al, 2012;Tedford et al, 2014).…”
Section: Consumer Tendernesscontrasting
confidence: 73%
“…Many Studies have shown that increased marbling level, or intramuscular fat (IMF%) was associated with greater tenderness, juiciness, flavour liking and overall liking (Lorenzen et al, 2003;Garmyn et al, 2011;Chriki et al, 2012;O'Quinn et al, 2012). Furthermore Thompson (2004) in cattle and in lamb found a positive relationship between IMF% and the flavour liking and juiciness scores of untrained Australian consumers.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the weaker structural properties of fat than other muscle tissue components (Thompson, 2004). These relationships are supported by O'Quinn et al (2012) who found that as the IMF% in the m. longissimus thoracis increased American untrained consumer scores for tenderness, flavour liking, juiciness and overall liking increased, though this effect was not consistent between the samples of beef derived from Australian and American cattle. This mirrors the findings of Thompson (2004), who also utilised untrained consumer panels and the m. longissimus thoracis.…”
mentioning
confidence: 97%